2024
DOI: 10.1039/d3ta05845j
|View full text |Cite
|
Sign up to set email alerts
|

A 3D-printed CuNi alloy catalyst with a triply periodic minimal surface for the reverse water-gas shift reaction

Wenbin Li,
Junhao Ding,
Xiao Chen
et al.

Abstract: Efficient enhancement of mass and heat transfer, as well as mechanical stability, has attracted particular interest for fixed-bed reactors in practical applications. In this study, monolithic CuNi alloy catalyst with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The CFD results showed that the TPMS structure significantly improved mass and heat transfer with a consistent turbulent flow in the 3D microchannels, and thereby exhibited 1.3 to 1.6 times higher catalytic activity than a honeycomb monolith. [28]…”
Section: Geometric Structurementioning
confidence: 99%
“…The CFD results showed that the TPMS structure significantly improved mass and heat transfer with a consistent turbulent flow in the 3D microchannels, and thereby exhibited 1.3 to 1.6 times higher catalytic activity than a honeycomb monolith. [28]…”
Section: Geometric Structurementioning
confidence: 99%
“…NiPt catalysts have shown great performance in reforming reactions [23,24] and decomposition of hydrazine for hydrogen production [25,26]. CuNi catalysts have been used for the ethanol decomposition reaction [27], furfural hydrogenation [28], CO oxidation [29], the water-gas shift reaction [30], as well as CuFe-catalysts, in the higher alcohol synthesis [31]. FePt nanoparticles have been used for CO oxidation [32], hydrogenation [33], and hydrodeoxygenation [34].…”
Section: Introductionmentioning
confidence: 99%